2018
DOI: 10.1039/c8ra02631a
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics and mechanism of pentoxifylline by ultraviolet activated peroxydisulfate

Abstract: Degradation of pentoxifylline (PTX) by sodium peroxydisulfate (SPDS) assisted by UV irradiation has been investigated in deionized water. The treatment was more favorable over direct photolysis or peroxydisulfate oxidation alone. The effects of various parameters, including different dosage of oxidant agent, PTX concentration, initial solution pH levels, and the presence of inorganic ions like chloride, nitrate and carbonate have been evaluated. The rate of PTX decomposition depends on the oxidant agent dose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…In regard to oxidative stress, our study showed that PTX degraded to multiple compounds (Figure S9). These results were consistent with the report by Kaminska and colleagues, 12 who identified one of the oxidative degradation products as 3,7-dihydro-3,7dimethyl-6-[(5-oxohexyl)oxy]-2H-purin-2-one, which we were able to acquire for the present study and found was one of the oxidative degradation products of PTX. By contrast, Mone and Chandrasekhar 10 identified one oxidative degradation product of PTX (1-(5,5-bishydroperoxy-hexyl)-3,7-dimethyl-3,7-dihydro-purine-2,6-dione), the further investigation of which was beyond the scope and focus of the present study.…”
Section: Stability-indicating Analysissupporting
confidence: 94%
See 3 more Smart Citations
“…In regard to oxidative stress, our study showed that PTX degraded to multiple compounds (Figure S9). These results were consistent with the report by Kaminska and colleagues, 12 who identified one of the oxidative degradation products as 3,7-dihydro-3,7dimethyl-6-[(5-oxohexyl)oxy]-2H-purin-2-one, which we were able to acquire for the present study and found was one of the oxidative degradation products of PTX. By contrast, Mone and Chandrasekhar 10 identified one oxidative degradation product of PTX (1-(5,5-bishydroperoxy-hexyl)-3,7-dimethyl-3,7-dihydro-purine-2,6-dione), the further investigation of which was beyond the scope and focus of the present study.…”
Section: Stability-indicating Analysissupporting
confidence: 94%
“…The results of forced degradation studies were consistent with previous reports [10][11][12] that PTX was stable under acidic stress and subject to significant degradation under alkali and oxidative stress (Table S1). As shown by Mone and Chandrasekhar, 10 we found that alkali stress led to PTX degradation to at least two compounds with prominent peaks at 2.2 and 2.5 min (compared to PTX at 6.3 min; Figure S8).…”
Section: Stability-indicating Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Comparison of photo-Fenton with persulfate and Fenton-like treatments of CY , E 0 = 2.60 V), which can be produced by activation of peroxodisulphate, are an alternative oxidant that has been lately studied as degradation agent for several organic pollutants (Ding et al 2017, Ismail et al 2017, Soltani and Lee 2017. Also, sulfate radicals present a longer life-time than hydroxyl radicals (Gao et al 2016) and are more selective towards organic substrates reacting via direct electron transfer mechanism (Kamińska et al 2018, Matta et al 2011. In this study, SO 4…”
Section: Effect Of H 2 O 2 Concentrationmentioning
confidence: 99%